Ethics in engineering research: an Islamic perspective - Ahsan, Muhammad Suhaib; Nuruzzaman, Md.; Al-Mamun, Abdullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The world is advancing very fast relying upon research and development (R&D) activities in produts processes. The engineering fields also rely heavily on R&D processes. Moreover, the advancement of engineering cannot be accomplished without continuous research to solve problems. The comparative and analytical methods were used in this paper. The important findings of this research paper are that the main misconducts in research are fabrication, plagiarism. Personal reason or strong believe in a matter and some other reasons have been identified as the reasons of misconducts in general research as well as engineering research. Regardless of the ideological differences between the western perspective and the Islamic perspective, both of those agreed on few things being wrong ways of research. Failure to overcome these misconducts in research may hamper producing quality outcome in every discipline, especially in engineering.